Prehospital troponin as a predictor of early clinical deterioration - Martín Rodríguez, Francisco (2021)
Background and Objectives: Elevated troponin T (cTnT) values are associated with comorbidities and early mortality, in both cardiovascular and noncardiovascular diseases. The objective of this study is to evaluate the prognostic accuracy of the sole utilization of prehospital point-of-care cardiac troponin T to identify the risk of early in-hospital deterioration, including mortality within 28 days. Methods: We conducted a prospective, multicentric, controlled, ambulance-based, observational study in adults with acute diseases transferred with high priority by ambulance to emergency departments, between 1 January and 30 September 2020. Patients with hospital diagnosis of acute coronary syndrome were excluded. The discriminative power of the predictive cTnT was assessed through a discrimination model trained using a derivation cohort and evaluated by the area under the curve of the receiver operating characteristic on a validation cohort. Results: A total of 848 patients were included in our study. The median age was 68 years (25th-75th percentiles: 50-81 years), and 385 (45.4%) were women. The mortality rate within 28 days was 12.4% (156 cases). The predictive ability of cTnT to predict mortality presented an area under the curve of 0.903 (95% CI: 0.85-0.954; P <.001). Risk stratification was performed, resulting in three categories with the following optimal cTnT cut-off points: high risk greater than or equal to 100, intermediate risk 40-100 and low risk less than 40 ng/L. In the high-risk group, the mortality rate was 61.7%, and on the contrary, the low-risk group presented a mortality of 2.3%. Conclusions: The implementation of a routine determination of cTnT on the ambulance in patients transferred with high priority to the emergency department can help to stratify the risk of these patients and to detect unknown early clinical deterioration.